A new genus Ittolemma (Heteroptera: Tingidae) gen. nov. and three included species of hirsute lace bugs from temperate woodlands of southern Australia. Issue 4 (14th April 2014) - Symonds, Celia L; Cassis, Gerasimos
Abstract A new Australian lace bug genus Ittolemma gen. nov. is described for the inclusion of three species. Tingis teretis Drake is transferred to the new genus Ittolemma, made the type species of the new genus and redescribed. Two new species – collected on recent Bush Blitz surveys in Western Australia – are described: I. credo sp. nov. and I. micula sp. nov. All species occur in temperate southern Australia from host plant genera in the families Lamiaceae and Scrophulariaceae (order Lamiales), including Eremophila. This work documents the first host plant records and a large range extension for I. teretis. A key to species, diagnostic images and notes on the generic placement within the Australian Tingidae fauna, is provided.